A Crisis of Ends: University Education as Formative Reading. (16th May 2016) - Lorkovic, Edvard
Abstract: Beginning with Mark C. Taylor's Crisis on Campus, and its critique of the structure and delivery of contemporary higher education, this essay argues that if there is a crisis in education, it is not technical, not reducible to the delivery of education. If there is a crisis, it lies in the contemporary world's misunderstanding of the goals or ends of the university. Borrowing Antonin's Sertillanges' account of reading from the Intellectual Life, the essay concludes by suggesting that the goal of university education is formation of the mind, not mastery, edification, of entertainment.